Zika-Associated Microcephaly Epidemic and Birth Rate Reduction in Brazilian Cities - Diaz-Quijano, Fredi Alexander; Pelissari, Daniele Maria; Chiavegatto Filho, Alexandre Dias Porto (American journal of public health (1971), 2018)
Objectives. To estimate birth reduction potentially in response to Zika virus–associated microcephaly among the 36 largest Brazilian cities. Methods. We analyzed the number of live births per month on the basis of information on approximately 8.2 million births from all of Brazil’s state capitals and cities that had more than 10 000 annual births. Results. In the second half of 2016, the live birth rate was reduced by 7.78% (95% confidence interval [CI] = 6.64%, 8.89%; P < .001). This reduction was correlated with the Zika virus–associated microcephaly rate. In the cities with the highest microcephaly rate in 2015 (> 1 case per 1000 live births), the reduction in the live birth rate was 10.84% (95% CI = 8.58%, 13.04%). Conclusions. The birth rate in the largest Brazilian cities during the second half of 2016 was significantly reduced, which is potentially the effect of a birth control recommendation prompted by an epidemiological alert. Public Health Implications. The effects of population-based interventions should be weighed by considering the actual risk of disease and the sociodemographic impact of strategies such as birth control.